Hydroxyacid Oxidase 2 (HAO2) Inhibits the Tumorigenicity of Hepatocellular Carcinoma and Is Negatively Regulated by miR-615-5p. (28th April 2022) - Li, Yuxuan; Zhang, Mingchao; Li, Xiuling; Wang, Yanyan; Wang, Yu; Li, Yuan; Zhu, Huihui; Ding, Hui; Li, Xiaofang; Sun, Suofeng
Abstract : Background . Hepatocellular carcinoma (HCC) is the sixth most common kind of cancer worldwide and the third leading cause of cancer mortality. Although a few studies have shown that hydroxyacid oxidase 2 (HAO2) may prevent HCC development, the molecular mechanism is unclear. Methods . We examined the levels of HAO2 expression in 23 pairs of HCC/paracancerous tissues by quantitative real-time polymerase chain reaction (qRT-PCR) and evaluated HAO2's expression in The Cancer Genome Atlas (TCGA) database. Furthermore, we examined the biological activity of HAO2 utilizing cell-based functional assays. Additionally, we evaluated the relationship between miR-615-5p and HAO2 in Hep3B cells using a dual-luciferase reporter system and assessed the downstream regulatory mechanisms of miR-615-5p on HAO2. Finally, the nude mice tumor formation experiment was used to determine the impact of HAO2 on the tumorigenicity of HCC cells. Results . HAO2 expression was considerably underexpression in HCC tissues and cells, and patients with low HAO2 expression had poorer disease-free survival. Inhibition of cell proliferation, migration, and invasion was observed when HAO2 was overexpressed. miR-615-5p had a negative relation with HAO2, and miR-615-5p restored HAO2's biological activity in HCC cells. Additionally, the tumor volume and weight were considerably reduced in the OV-HAO2 group compared to the OV-NC group. Conclusion . HAO2 was found to be underexpressed in HCC tissues and cells, and HAO2 overexpression inhibited HCC cell motility, which was negatively regulated by miR-615-5p. Exogenous expression of HAO2 reduced the tumorigenicity of HCC cells in vivo in nude mice.